2017
DOI: 10.1111/liv.13528
|View full text |Cite
|
Sign up to set email alerts
|

Trends in HCV treatment uptake, efficacy and impact on liver fibrosis in the Swiss HIV Cohort Study

Abstract: After the introduction of second-generation DAAs, we observed an increase in treatment uptake and efficacy which resulted in a significant reduction in the number of cirrhotic patients with a replicating HCV infection in the SHCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Data are from 2014 to 2015. Second‐generation DAAs were available but restricted by liver disease stage .…”
Section: Results ‐ Progress Toward Hcv Elimination In Hiv‐infected Pomentioning
confidence: 99%
See 2 more Smart Citations
“…Data are from 2014 to 2015. Second‐generation DAAs were available but restricted by liver disease stage .…”
Section: Results ‐ Progress Toward Hcv Elimination In Hiv‐infected Pomentioning
confidence: 99%
“…Population-wide proportions of those diagnosed with HIV/HCV co-infection who have received treatment are likely to be lower than those presented here. HCV diagnosis rates among HIV-infected populations are not currently well understood and additional research is required to estimate [42]. c Cascade of care from the ATHENA cohort of people diagnosed with HIV in the Netherlands from a period where DAAs were broadly available but prior to MC Free, Amsterdam [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed clinical and laboratory data were recorded at study entry and every 6 months thereafter. HCV infection assessments included yearly serology followed by HCV RNA determination in seropositive individuals, as well as a detailed treatment history, as described previously [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…Achieving a sustained virological response (SVR) substantially reduces HCV-related mortality and morbidity and prevents further HCV transmission [ 2 ]. After the approval of interferon-free second-generation direct-acting antivirals (DAAs) in Switzerland, we observed a 4-fold increase in treatment uptake and a 2-fold increase in treatment efficacy, with an SVR rate above 90% across all HCV genotypes [ 3 ]. Previous modeling studies indicated that a major increase in DAA treatment uptake has the potential to curb the HCV epidemic [ 4 , 5 ].…”
mentioning
confidence: 99%